1999
DOI: 10.1055/s-1999-2706
|View full text |Cite
|
Sign up to set email alerts
|

New Feature of Friedel-Crafts Phosphonation of Anisoles: Unexpected In Situ Methylphosphorylation Reaction

Abstract: Anisoles 1, reacting with AlCl 3 and PCl 3 with appropriate reagent ratios, give, in good yields, the corresponding diaryl methylphosphonates 2 or the methylphoshinates 3b,c and the methylphosphine oxides 4b,c. This unexpected in situ methylphosphorylation explains the reported limited and conflicting results to obtain methoxy-substituted arylphosphonous dichloride with the same reagents. A suggested mechanism is also reported.Since the last century, the Friedel-Crafts-type reaction 1 using PCl 3 and AlCl 3 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…The formation of such intermediates is favoured by the "dibenzo-butterfly" structure of 1, as we reported for the synthesis of cyclic tertiary phosphanes. [31] It is noteworthy that previously [25,31] we thought that the hexacoordinate intermediate AЈ required a nucleophilic attack, for example, by water or an acid in order to decompose it. During this study, however, we observed by 31 P NMR spectroscopy that AЈ is unstable and spontaneously collapses to give the corresponding tertiary phosphanes, presumably due to its high steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of such intermediates is favoured by the "dibenzo-butterfly" structure of 1, as we reported for the synthesis of cyclic tertiary phosphanes. [31] It is noteworthy that previously [25,31] we thought that the hexacoordinate intermediate AЈ required a nucleophilic attack, for example, by water or an acid in order to decompose it. During this study, however, we observed by 31 P NMR spectroscopy that AЈ is unstable and spontaneously collapses to give the corresponding tertiary phosphanes, presumably due to its high steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
“…[31] It is noteworthy that previously [25,31] we thought that the hexacoordinate intermediate AЈ required a nucleophilic attack, for example, by water or an acid in order to decompose it. During this study, however, we observed by 31 P NMR spectroscopy that AЈ is unstable and spontaneously collapses to give the corresponding tertiary phosphanes, presumably due to its high steric hindrance. Consequently, about 30-40 min after the addition of the last Grignard reagent, BH 3 ·THF can be added to the reaction mixture to form complexes of the tertiary phosphanes formed by the spontaneous decomposition of AЈ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, after several studies on the structure of the other products, we found [7] that, when the reaction is carried out under appropriate reaction conditions, an unexpected ''insertion'' of a phosphorus moiety into the OϪMe bond of anisole 4 occurs, to give compound 8 as the major product in place of the expected FriedelϪCrafts phosphonation (Scheme 4). The best selective formation of 8 (50Ϫ70% yield) was obtained with an anisole 4/AlCl 3 /PCl 3 ratio of 1:0.6:1, at 70Ϫ80°C for 7Ϫ10 h under dry nitrogen and without solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Results obtained from the reaction of anisole and AlCl 3 / PCl 3 in different ratios of the reagents A suggested mechanism, depicted in Scheme 5, for this phosphorus insertion reaction was also reported. [7] The insertion of a P moiety is explained by the attack of a molecule of PCl 3 on an anisoleϪAlCl 3 complex and subsequent migration of the methyl group to the same P atom giving the intermediate AЈ. Subsequent nucleophilic attack of free anisole on phosphonium salt AЈ gives BЈ which, after quenching with water, gives phosphonate 8.…”
Section: Resultsmentioning
confidence: 99%